2005
DOI: 10.4161/cbt.4.10.2023
|View full text |Cite
|
Sign up to set email alerts
|

High frequency somatic mutations in RASSF1A in nasopharyngeal carcinoma

Abstract: High frequency loss of 3p21.3 region is a common event in various kinds of tumors including nasopharyngeal carcinoma (NPC). RASSF1A has been identified as a putative tumor suppressor gene residing in this region. Chromosome alterations and epigenetic changes are commonly observed as mechanisms for inactivation of RASSF1A function. In this study, we applied the PCR-cloning-sequencing strategy to examine somatic mutations in RASSF1A in NPC tissues as compared with the sequences detected in the matched peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
(56 reference statements)
1
34
0
Order By: Relevance
“…Most of these mutations are located in functional domains of RASSF1A. Recently, using a more sensitive methodology, a high incidence of RASSF1 mutations were found in primary NPC tumours (Pan et al, 2005). Interestingly, however, expression of RASSF1A, but not RASSF1C, is lost or downregulated in a variety of tumours.…”
Section: Rassf1mentioning
confidence: 99%
“…Most of these mutations are located in functional domains of RASSF1A. Recently, using a more sensitive methodology, a high incidence of RASSF1 mutations were found in primary NPC tumours (Pan et al, 2005). Interestingly, however, expression of RASSF1A, but not RASSF1C, is lost or downregulated in a variety of tumours.…”
Section: Rassf1mentioning
confidence: 99%
“…Ras-association domain family 1 isoform A (RASSF1A), encoded by the RASSF1 gene, is one of the most epigenetically silenced elements in human cancers and consists of a diacylglycerol -binding domain, a Ras-association domain, and an ATM kinase phosphorylation consensus motif (Pan et al, 2005;Amin & Banerjee, 2012). To the best of our knowledge, RASSF1A is functionally implicated in a variety of key biological processes, including cell cycle regulation, microtubule stabilization, and cellular adhesion and mortality, as well as apoptosis (Abouzeid et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that some genes are high frequently methylated in tumor tissue DNA obtained from NPC primary tumors, but not in normal tissues (Pan et al 2005;Sun et al 2007;Zhang et al 2007;Li, Shu, et al 2011). These genes are ideal candidate to serve as biomarkers for detection of NPC.…”
Section: Dna Methylation Results From Tumor Tissuesmentioning
confidence: 99%